Behavioral threat and appeasement signals take precedence over static colors in lizard contests - Abalos, Javier; de Lanuza, Guillem; Bartolome, Alicia; Liehrmann, Oceane; Aubret, Fabien; Font, Enrique (Oxford University Press, 2025)
The interplay between morphological (structures) and behavioral (acts) signals in contest assessment is still poorly understood. During contests, males of the common wall lizard (Podarcis muralis) display both morphological (i.e. static color patches) and behavioral (i.e. raised-body display, foot shakes) traits. We set out to evaluate the role of these putative signals in determining the outcome and intensity of contests by recording agonistic behavior in ten mesocosm enclosures. We find that contests are typically won by males with relatively more black coloration, which are also more aggressive. However, black coloration does not seem to play a role in rival assessment, and behavioral traits are stronger predictors of contest outcome and winner aggression than prior experience, morphology, and coloration. Contest intensity is mainly driven by resource- and self-assessment, with males probably using behavioral threat (raised-body displays) and de-escalation signals (foot shakes) to communicate their willingness to engage/persist in a fight. Our results agree with the view that agonistic signals used during contests are not associated with mutual evaluation of developmentally-fixed attributes, and instead animals monitor each other to ensure that their motivation is matched by their rival. We emphasize the importance of testing the effect of signals on receiver behavior and discuss that social recognition in territorial species may select receivers to neglect potential morphological signals conveying static information on sex, age, or intrinsic quality.Behavioral signals outweigh static color patches in determining the winner of territorial disputes. To understand what limits aggression in wall lizards, we recorded social behavior in 10 experimental enclosures. We found that raised-body displays and foot shakes are better predictors of contest outcome than color patches, possibly because lizards use dynamic threat and de-escalation signals to communicate their motivation to engage/persist in a fight, while coloration conveys more general information about sex, age, and quality.